Data Quality Management in International Distribution Company - Nekula, Petr; Potančok, Martin; Matějka, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
This thesis describes the analysis, design, and implementation of a pilot Data Quality Management solution undertaken within the pan-European business environment of a global company. The main objective of the pilot project was to deliver an end-to-end data quality management solution within a well-defined scope, aimed at supporting the business in gaining benefits from continuous data quality improvements. The expected long-term business benefits are to support the company in increasing its internal efficiency, and to improve its customer services. This thesis describes all phases of the pilot solution development and delivery, starting with an introduction of the company, its business environment, and its data and analytics landscape. This is followed by an analysis of the existing data quality issues, and the business requirements for addressing their resolution. Thereafter follows a description of the solution design wherein the key components, delivery approach, technology, and target state architecture are defined. The thesis continues with a description of the implementation of the solution components – starting with new data quality processes, continuing with a new data quality measurement framework, and finishing with a new data quality dashboard. Finally, the thesis closes with an evaluation of the delivered solution against the business requirements and success criteria, and a description of the future required support for data quality improvement in the long-term, together with recommendations for solution enhancements to follow the pilot phase. This thesis provides a full and detailed description covering the reality of an actual real-life data quality management project in the aforementioned company.
The information and experience shared herein may hopefully prove useful to other Data Management professionals who are planning the launch of their own data quality initiatives, either through leverage of the detail of the described practices, or by gaining some inspiration on the options of how to approach such a project within their own specific environments.
Vedoucí práce: Martin Potančok
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet